Didactic exercises. A way to improve the simple direct attacks in the karatecas of the school category. - Yanet Castillo-Corbacho; Juan Carlos Pérez-Pelegrin (Universidad de Guantánamo, 2018)
The work has been conceived with the objective of improving the simple direct attacks in the karatecas of the school category in the Sport Integral School of the county Guantánamo through a group of didactic exercises. As part of the tactical preparation, they took into account methods of the empiric level, of the theoretical level, of the mathematical level, approaches referred to the tactics, with the same ones were possible to consolidate even more the diagnosis of the existent problem, as well as the necessary tools for the proposal to carry out. For the evaluation of the feasibility of the proposal was used the pre-experiment method.